DIVERSITY AND STATUS OF BUTTERFLIES IN AWASIAN WATER FOREST RESERVE, MT. HILONG-HILONG, PHILIPPINES - Arturo Grasia; Mary Cris G. Abao; Kevin C. Quiňonez; Mark Freddie D. Suarez; Lea Jane G Elegio; Alma B. Mohagan (BIOTROPIA, 2022)
Butterflies are deemed as an essential faunal group in the ecosystem due to their ecological services. However, continuous habitat loss leads to the decline of its population. Thus, this study was conducted to assess its diversity and status in one of the Watersheds of Mt. Hilong-hilong. Sweep netting (336 man-hours) and butterfly trapping (200 trap days) were carried out to document the species. Fifty-seven species of butterflies were recorded with the family Nymphalidae as the most represented group (n = 30). Species diversity (H') was relatively higher in Dipterocarp (H' = 1.49) forest than Agroecosystem (H' = 1.39), a result primarily influenced by favorable ecological support like food availability. Endemicity was 31%, which comprised mostly of rare species. Noteworthy findings are the listing of globally and nationally rare species but locally assessed as common. Based on the results, the area harbors an array of butterfly species and various rare species that requires an effective management plan to conserve the organisms.